Genetic resources of traditional pear varieties in the region of Povardarie - Miskoska-Milevska, E.; Selamovska, A. (Ecological Movement of Novi Sad, 2018)
In this study, we researched the phenological characteristics, fruit physical and chemical characteristics in 9 traditional pear varieties (Carigradsko avche, Evropsko avche, Letna kajkushka, Karamanka, Drvenjak, Vodenka, Tiranka, Zimnica and Zimska kajkushka) in the Povardarie region. The pears Drvenjak and Zimnica in Skopje have the biggest fruits. The variety Zimska kajkushka contains high quantity of seeds in the fruits. The varieties Evropsko avche, Drvenjak, Karamanka, Tiranka and Vodenka have long fruit stalks. The high value of soluble dry matter was presented in Drvenjak, Tiranka, Zimska kajkushka and Zimnica. Statistically significant differences among the examined pear varieties for all fruit characteristics were found. The varieties Vodenka and Karamnaka gave fruits with the highest quality and taste.
Keywords: pear, traditional variety, fruit characteristics, Povardarie region